2010
DOI: 10.1126/science.1190333
|View full text |Cite
|
Sign up to set email alerts
|

Species Interactions in a Parasite Community Drive Infection Risk in a Wildlife Population

Abstract: Most hosts, including humans, are simultaneously or sequentially infected with several parasites. A key question is whether patterns of coinfection arise because infection by one parasite species affects susceptibility to others or because of inherent differences between hosts. We used timeseries data from individual hosts in natural populations to analyze patterns of infection risk for a microparasite community, detecting large positive and negative effects of other infections. Patterns remain once variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
574
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(586 citation statements)
references
References 24 publications
7
574
4
1
Order By: Relevance
“…In voles, the infections are usually subclinical and persistent . The risk of infection depends on coinfection with other parasite species (Telfer et al 2010), however in the current paper, we found no such interactions.…”
Section: Infections and Survivalcontrasting
confidence: 53%
See 1 more Smart Citation
“…In voles, the infections are usually subclinical and persistent . The risk of infection depends on coinfection with other parasite species (Telfer et al 2010), however in the current paper, we found no such interactions.…”
Section: Infections and Survivalcontrasting
confidence: 53%
“…Significant effects of alleles after controlling for false discovery rate are marked with asterisks. b parameter estimate, df degrees of freedom, v 2 statistics, p probability Evol Ecol (2013) 27:635-653 647 represent the sole explanation for the increased mortality of infected animals (Telfer et al 2010), and their effect on host populations often depends on other factors, such as host sex (Fuller and Blaustein 1996) or food availability (Murray et al 1996). Here, we studied survival over the winter, which is the period when the tight energy budget of animals may make the negative effects of parasite infection particularly pronounced.…”
Section: Infections and Survivalmentioning
confidence: 99%
“…Furthermore recent studies have provided evidence that interaction between tick-borne pathogen populations can influence TBD epidemiology. This can be manifest in a positive or negative manner and alter pathogen prevalence, pathogen transmission, and host susceptibility (Ginsberg 2008;Telfer et al 2010). Therefore, to gain fuller insight into the factors that influence risk from tick-borne disease, future studies should attempt to capture data on interacting parasite communities rather than individual parasite species.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite-host relationships are shaped by a multitude of interacting factors, including host availability, parasite community structure (Jolles et al 2006;Telfer et al 2010), and environmental heterogeneity at multiple scales (Biek and Real, 2010).…”
mentioning
confidence: 99%